Sources and rates of boron in rubber rootstocks - Moreira, Adônis; Moraes, Vicente Haroldo de Figueiredo; Castro, César de (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effect of boron supply on the increment of stem diameter, number and diameter of lateral roots and the nutritional status of rubber rootstocks at the budding height (5 cm above the root collar), for the production of base root budded stumps, in a Xanthic Ferralsol. The experimental design was in randomized blocks, in a 2x5 factorial scheme: two sources (ulexite – 10% of B and boric acid – 17% of B) and five B rates (0, 2, 4, 8 and 16 kg ha-1), with four replicates. Under the local conditions, the response curves showed significant increases in increment of stem diameter at 6.5 and 16 kg ha-1 B, and in the number of lateral roots at 13.9 and 16 kg ha-1 B, with boric acid and ulexite, respectively. The B rate did not improve the number of lateral of roots. The critical level of boron in leaf of rubber rootstocks obtained with boric acid is 31.8 mg kg-1. The B rates supply presented significant interactions with the leaf contents of B, Mn and Zn, while leaf contents of N, P, K, Ca, Mg, S, Na, Cu and Fe did not vary in function of B rates.